82.4k views
24 votes
What's substitution for y=4x-1, 2x+y=5

User BrownEye
by
4.6k points

2 Answers

10 votes

Explanation:

y = 4x-1

2x+y = 5

2x+(4x-1) = 5

6x - 1 = 5

6x = 6

x = 1

User Konsolas
by
5.1k points
2 votes

Answer:

(1,3)

Explanation:

Since we already have the variable to it self, we can substitute y=4x-1 into 2x+y=5.

So it would be 2x+(4x-1)=5

Remove the parentheses

Combine like terms

Move the constant to the right

Divide 6 on both sides to get the variable by it self.

x=1

Then we substitute x=1 into y=4x-1, so..

y=4(1)-1

y=4-1

y=3

So the answer would be (1,3).

Hoped it helped!

User SooCheng Koh
by
4.6k points